The NPP and social asset impacts of acidification from coal-fired power plant in Thailand - Rewlay-ngoen C. (Elsevier Ltd, 2014)
Since 1978, coal has played an important role in power generation systems in Thailand, and in 2013 it accounts for 19% of the total electricity production of the whole country. However, coal-fired power plants are by far the biggest sources of sulfur dioxide (SO2) emitted into the atmosphere, which contributes to the formation of acidification and directly affects terrestrial ecosystems and materials. In addition, when the acid level (pH) of rainfall reduces, it changes the soil's physical and chemical characteristics and affects the growth rate of the plants. On the other hand, acidity rainfall on buildings causes metal and stone damage and destruction. Therefore, the understanding of the environmental impacts of electricity generation from coal is needed. It can lead to the development of acidification reduction plans and policies. Life Cycle Impact Assessment (LCIA) is one of the useful tools for evaluating the environmental burden of processes by accounting for the inflow and outflow of materials and energy as well as the waste released into environment. Thus, the main objective of this study was to analyses the acidification damage factor from coal-fired power plants using Life-cycle Impact assessment Model based on Endpoint modelling (LIME). As the results, the endpoint effects of acidification indicated that it will definitely and seriously destroy the growth rate of plants and be able to show this in terms of the value of Net Primary Production (NPP) and damage to the building can be shown via the maintenance social assets cost (Baht). Moreover, the results will help us to minimize the acidification damage costs from coal-fired power plants to be more environmentally friendly. © 2014 Published bv Elsevier Ltd.